1981
DOI: 10.1111/j.1365-4362.1981.tb00847.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Single and Multiple Applications of Halcinonide Cream

Abstract: A double-blind paired comparison was made of once daily and three times daily regimens of 0.1% halcinonide cream in 149 patients with atopic dermatitis and 194 with psoriasis. In a simultaneously conducted study once daily application of 0.1% halcinonide was compared to the cream base alone (placebo) in 48 patients with atopic dermatitis and 78 with psoriasis. Results show that a once daily regimen can be an effective treatment in both conditions, and can be recommended as a starting regimen in certain circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Hoare and colleagues reviewed the 3 trials comparing once-daily vs more frequent use of the same topical corticosteroids. [2][3][4] In none of the trials were more frequent applications superior to once-daily applications. These observations should be kept in mind for cost and compliance considerations.…”
Section: Editor's Commentmentioning
confidence: 92%
“…Hoare and colleagues reviewed the 3 trials comparing once-daily vs more frequent use of the same topical corticosteroids. [2][3][4] In none of the trials were more frequent applications superior to once-daily applications. These observations should be kept in mind for cost and compliance considerations.…”
Section: Editor's Commentmentioning
confidence: 92%
“…However, when using topical corticosteroids of lower ranks or changing to drugs without corticosteroids, it is necessary to confirm that there is no recurrence by changing to an intermittent pattern such as alternate‐day or once‐a‐day application. With regards to topical corticosteroids at the rank higher than the strong class, there is not a significant difference between twice‐a‐day application and once‐a‐day application in curative effects after 3 weeks (evidence level II: by one or more randomized controlled trials) 31,32 . Considering the fact that side‐effects diminish as the application times decrease, it is preferable to apply twice a day in an acute exacerbation to sedate the inflammation quickly and to apply once a day after improvement of the eruption (recommendation grade A: strongly recommended to perform).…”
Section: Treatmentmentioning
confidence: 99%
“…For the treatment of dermatitis, recent studies revealed no difference between once and twice daily application or slight differences which are probably not of clinical significance. 20,21 Both were paired comparison investigations with one study showing no difference except for a relatively more rapid onset of action. 18 Both treatments significantly reduced all clinical features equally, but the clearance rate was significantly higher with the twice daily regimen.…”
Section: Efficacy Of Corticosteroidsmentioning
confidence: 99%